A Qualitative Examination of How Somali Young Adults Think About and Understand Violence in Their Communities. Issue 1 (January 2022) - Ellis, B. Heidi; Decker, Scott H.; Abdi, Saida M.; Miller, Alisa B.; Barrett, Colleen; Lincoln, Alisa K.
Violence prevention efforts must take into consideration the potentially stigmatizing labels associated with violence, and how youth perceive different types of violence in their communities. Somali communities and individuals in North America have at times been labeled as at-risk for violence, with two notable examples being gang violence and ideologically motivated violence, or violent radicalization. Little is known, however, about how the youth themselves think about and understand these types of violence in their communities. In this article, we seek to answer the following questions: How do Somali immigrants think about violence in their communities, and the stigma related to this violence? and What are the implications of these perceptions/beliefs for violence prevention? Data are drawn from two qualitative studies conducted as part of an ongoing community-based participatory research (CBPR) collaboration between academic partners and Somali communities in three cities in North America. Study 1 consists of nine focus groups ( n = 36, male only), and Study 2 consists of in-depth interviews ( n = 40, male and female). All participants are Somali young adults living in North America. Overall, radicalization to violence is seen as a remote and irrelevant issue in the Somali community. Participants distance themselves from the idea of radicalization to violence and from those who participate in radical acts or held such beliefs. In contrast, gang involvement is characterized as a major problem for Somali communities, and a product of the marginalization associated with being a refugee in Canada or the United States. Findings suggest that prevention efforts focused on gangs are more likely to be acceptable to communities than those focused on violent extremism.